Constipation and risk of cardiovascular diseases: a Danish population-based matched cohort study. Issue 9 (1st September 2020) - Sundbøll, Jens; Szépligeti, Szimonetta Komjáthiné; Adelborg, Kasper; Szentkúti, Péter; Gregersen, Hans; Sørensen, Henrik Toft
Abstract : Objectives: To assess the risks of myocardial infarction, stroke, peripheral artery disease, venous thromboembolism, atrial fibrillation or atrial flutter and heart failure in patients with constipation compared with a general population cohort. Design: Population-based matched cohort study. Setting: All Danish hospitals and hospital outpatient clinics from 2004 to 2013. Participants: Patients with a constipation diagnosis matched on age, sex and calendar year to 10 individuals without constipation from the general population. Main outcomes measures: Comorbidity-adjusted and medication-adjusted hazard ratios (aHRs) for cardiovascular outcomes based on Cox regression analysis. Results: 83 239 patients with constipation were matched to 832 384 individuals without constipation. The median age at constipation diagnosis was 46.5% and 41% were men. Constipation was strongly associated with venous thromboembolism (aHR 2.04, 95% CI 1.89 to 2.20), especially splanchnic venous thrombosis (4.23, 95% CI 2.45 to 7.31). Constipation was also associated with arterial events, including myocardial infarction (1.24, 95% CI 1.14 to 1.35), ischaemic stroke (1.50, 95% CI 1.41 to 1.60), haemorrhagic stroke (1.46, 95% CI 1.26 to 1.69), peripheral artery disease (1.34, 95% CI 1.20 to 1.50), atrial fibrillation or atrial flutter (1.27, 95% CI 1.20 to 1.34) and heart failure (1.52, 95% CI 1.42 to 1.62). The associations were strongest during the first year after the constipation diagnosis and strengthened with an increased number of laxative prescriptions. Conclusions: Constipation was associated with an increased risk of several cardiovascular diseases, in particular venous thromboembolism.